2018
DOI: 10.1039/c8nr02190b
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an all-optically controlled dynamic superlattice for exciton–polaritons

Abstract: Exciton-polaritons, formed by the strong coupling between excitons and cavity-confined photons, are the building blocks of polaritonic devices. In this work, we report experimental realization of an all-optically controlled dynamic superlattice for polaritons working in the ultraviolet wavelength range at room temperature. The optical superlattice was realized on a one-dimensional (1D) ZnO microrod using an array of periodically arranged laser spots. Polaritonic mini-band features were clearly observed by both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…They have very smooth hexagonal cross sections which support WG resonant modes for light fields, as shown schematically in Figure b. Exciton-polaritons are formed due to the strong coupling between these WG modes and the excitonic states. , A typical angle-resolved photoluminescence (PL) image of such microrods is shown in Figure b. The formation of polaritons is evidenced by the excellent agreement between the emission pattern and the theoretical dispersion (dashed curve) fitted using the coupled-oscillator model.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…They have very smooth hexagonal cross sections which support WG resonant modes for light fields, as shown schematically in Figure b. Exciton-polaritons are formed due to the strong coupling between these WG modes and the excitonic states. , A typical angle-resolved photoluminescence (PL) image of such microrods is shown in Figure b. The formation of polaritons is evidenced by the excellent agreement between the emission pattern and the theoretical dispersion (dashed curve) fitted using the coupled-oscillator model.…”
mentioning
confidence: 70%
“…While their photonic component makes them extremely light particles, their inherited excitonic component gives them the ability to interact with other charge carriers via Coulomb forces. Nowadays, it is generally known that these polaritonic Coulomb interactions essentially govern the dynamics and optical properties of exciton-polaritons. , Many of the fascinating phenomena, such as quantized vortices and tunable magnetic alignments, are closely related to the polariton–polariton interactions. A comprehensive understanding of such polaritonic interactions is thus of fundamental importance.…”
mentioning
confidence: 99%
“…The samples we used are one-dimensional ZnO microrods grown by chemical vapor deposition method. Having smooth facets and hexagonal cross-sections, such microrods form natural whispering gallery (WG) microcavities for the confinement of light field [17,24,37,38]. The intrinsically large excitonic binding energy (∼ 60 meV at room temperature) and oscillator strength make them a promising testing bed for experimental studies of polaritonics, as demonstrated in our previous work [17,24,39].…”
mentioning
confidence: 91%
“…Such a system has so far been realized in a set of vertically coupled planar microcavities [21,28] or a semiconductor microrod. [29][30][31][32] Offering a high degree of tunability, vertically coupled microcavities have been studied mostly in the linear regime, [23,28,[33][34][35][36][37] while the non-linear regime was addressed in the exclusive context of resonantly driven parametric scattering. [20,21] In particular, such fundamental effects as polariton condensation and lasing, or parametric polariton scattering under non-resonant excitation, have so far not been observed and studied in a vertically coupled, planar microcavity system.…”
Section: Introductionmentioning
confidence: 99%